MUSYARAKAH MUTANAQISHAH - ‘Ainul Imronah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
The expense and finance are products which are issued by sharia financial institutions,includingmusharakamutanaqishah. Musharakamutanaqishah is a form of cooperation between two or more parties for the ownership of goods or assets. This cooperation will reduce the ownership rights of one party while the other party increases its ownership rights. This article is purposed to give knowledge to whom do not understand well about Musyarakahmutanaqishah. The nature of the research is descriptive which used literature study in collecting the data. The technique of Data analysis is used qualitative analysis. The results of the study are the definition, the history and the root of musyarakahmutanaqishah, the provision of musyarakahmutanaqishah law, the terms of the contract, the provisions of the related parties, the criteria of the customer, the financing scheme, the advantages and the weaknesses of Musyarakahmutanaqishah, the ownership of syirkah modality and the ending of syirkah.